Teenage pregnancy and mental health in Africa: A bibliometric analysis - Hoque, Muhammad (Orapuh Journal, 2025)
Introduction Adolescent pregnancy is a significant public health and societal challenge in Africa, with far-reaching implications for young people’s mental well-being. Purpose This study aimed to analyse research trends, geographic patterns, and thematic focuses on teenage pregnancy and mental health in Africa using bibliometric methods. Methods A bibliometric analysis was conducted using PubMed/MEDLINE, Scopus, and SABINET databases, covering the period 2014–2023. Relevant peer-reviewed journal articles focusing on adolescent pregnancy and mental health were analysed with VOSviewer to assess publication trends, co-authorship, keyword co-occurrence, and citation impact. Results A total of 257 articles met the inclusion criteria, showing a sharp rise in research activity after 2015. Most studies originated from South Africa (27.1%), Nigeria (18.3%), and Kenya (13.1%), while Central and North Africa had low output. The main topics studied were depression (72%), anxiety (58%), post-traumatic stress disorder (41%), and suicidal ideation (29%). Commonly cited socio-economic risk factors included poverty, intimate partner violence, and inadequate reproductive health education. Citation analysis indicated generally moderate research impact and limited inter-country collaboration, with only 15.8% of studies involving non-African authors. Despite the growth in publications, only 14% evaluated interventions, and few addressed school-based or digital mental health approaches. Conclusion While research on teenage pregnancy and mental health in Africa has increased, regional and thematic gaps persist. Future work should emphasise intervention studies, longitudinal designs, and broader geographic coverage.